Improving The Ability of Students in Listening Comprehension by Using Authentic Materials - Gusnadi, Gusnadi; Sutisna, Entis; Supriyanto, Ahmad (Fakultas Keguruan dan Ilmu Pendidikan Universitas Pakuan, 2023)
Listening is one of the receptive skills in English. Therefore, the problem is concerned with the lack of students’ listening skills. Thus, this research is aimed to prove that creative methods can help students to build their ability in listening. This research is conducted to the second semester of English Language Education Study Program Faculty of Teacher Training and Education Sciences, Pakuan University. In choosing the sample, the technique of total sampling is used. the quasi-experimental research design is applied in this research. The design of the research was pre-test and post-test that were given to the experimental and control group. The result of the data analysis showed a significant difference. By applying 0,05 level of significance and the degree of freedom (df) is 44, it showed that the t-counted 1,11 was lower than t-table 2,02. In conclusion, the use of authentic materials is not affected to improve the students’ listening comprehension.